The Effect of Moringa-Based Supplementation on Fetal Birth Weight in Jeneponto Regency - Andi Imam Arundhana; Muhammad Syafruddin Nurdin; Veni Hadju; Ansariadi; Andi Zulkifli (Journal of Pharmacy and Nutrition Sciences, 2018)
Background: Low birth weight (LBW) is one of the main causes of morbidity and mortality besides preterm birth. Proper interventions during pregnancy can prevent an adverse pregnancy outcome. This study aims to see the effect of Moringa leaf capsule on birth weight. Methods: This study was double blind randomized controlled trial (DB-RCT) which consisted of three groups namely, Moringa powder (PG), Moringa extract (EG), and iron-folate (IG) groups. The intervention was given for 12 weeks. The samples were 453 pregnant women in six sub-districts in Jeneponto Regency. Data on birth weight and placental weight were measured by trained midwives. The weight of the placenta was measured to determine the placental ratio to birth weight. In addition, some socio-economic variables such as age, gestational age, eating frequency, smoking, and Hb levels were measured in this study. Logistic and linear regression were conducted in this study. Result: The Moringa leaf supplementation groups (PG and EG) delivered child with better weight than iron supplementation (3240.03±453.82, 3161.91±527.70, 3100.89±412.15, respectively). The placenta to birth weight ratio (PBWR) showed that IG group became lowest, merely 16.19%. The most influenced factor to LBW is the unhappiness of the women with her pregnancy (OR = 26.3, 95% CI = 1.227 - 566.474, p = 0.037). Conclusion: Moringa powder supplementation can be used as an alternative in improving new born baby weight. Pregnant women need to be happy and avoid stress to prevent LBW.